Influence of Knowledge Sharing, Engagement, and Spirituality on Employee Performance at Kualuh Selatan District Office - Munthe, Yusromuin; Nasution, Yenni Samri Juliati; Yanti, Nursantri (Sekolah Tinggi Ilmu Ekonomi Amkop Makassar, 2025)
This study uses a quantitative method with an associative approach to examine the influence of knowledge sharing, employee engagement, and workplace spirituality on employee performance. The research was conducted at the Kualuh Selatan Subdistrict Office, Labuhanbatu Utara Regency, involving 35 respondents. Data were collected through questionnaires that had been tested for validity and reliability. The validity test confirmed that all instrument items were appropriate, and a Cronbach’s Alpha value of 0.708 indicated good internal consistency. Data analysis was carried out using multiple linear regression to determine the partial and simultaneous influence of the three independent variables on employee performance. The findings reveal that knowledge sharing, employee engagement, and workplace spirituality all have a positive and significant effect on performance. Employee engagement was found to have the most dominant influence, followed by knowledge sharing and workplace spirituality. The F-test showed the regression model is simultaneously significant, and the coefficient of determination (R²) value of 0.621 indicates that the model explains 62.1% of the variation in employee performance. These results highlight the importance of enhancing work engagement, knowledge collaboration, and spiritual values to improve performance in public sector organizations.